Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Problem Based Learning Untuk Siswa SMP Kelas VII Pada Mata Pelajaran IPA - Zuliarni; ririn rahma weni; Meldi Ade Kurnia Yusri; Eldarni (Universitas Negeri Padang, 2023)
This study aims to produce Student Worksheets (LKPD) Based on Problem Based Learning in Science Subjects on environmental pollution at SMPN 2 Bayang Utara and to find out students' responses to the developed LKPD. The research method used is research and development (Reseach and Development) with the ADDIE development model developed by Dick and Carry. This research has 5 stages, namely: Analysis, Design, Development, Implementation, and Evaluation. The product validation test was carried out by 3 validators consisting of 2 media expert validators and 1 material expert validator. Product trials were carried out on 14 students of SMPN 2 Bayang Utara with the aim of knowing the practicality of the product being developed. The results showed that the product produced was